Assessing the Economic Implications of Sustainable Tourism Development in the Coastal Areas of Sundarbans, West Bengal - Dr Prodipta Barman; Dr Papiya Golder; Dr Joydeb Patra; Dr Tamal Gupta; Ms Maitrayae Sadhu; Ms Manisha Naskar (The Bioscan, 2025)
The Sundarbans, a UNESCO World Heritage Site, represent the world's largest mangrove forest, spanning the coastal regions of West Bengal, India, and Bangladesh. This study examines the interplay between sustainable tourism and economic growth in the Sundarbans, focusing on the Indian segment. The region's rich biodiversity, including the Royal Bengal Tiger and diverse avifauna, positions it as a prime ecotourism destination. However, the area faces challenges such as environmental degradation, loss of species, and pollution, which threaten its ecological balance. A SWOT analysis reveals that while the Sundarbans possess significant strengths—such as unique cultural heritage and established tourism infrastructure—there are notable weaknesses, including inadequate coordination among local communities and limited economic benefits from tourism. Opportunities exist in developing eco-friendly tourism packages, involving local populations in decision-making, and diversifying tourism products to enhance income retention within the community. Conversely, threats encompass potential environmental impacts, pollution, and increased biotic pressure due to mass tourism. The study underscores the necessity for a multi-stakeholder approach to sustainable tourism development in the Sundarbans. Additionally, promoting environmental awareness, establishing eco-friendly infrastructure, and ensuring equitable distribution of tourism-generated income are vital for the region's long-term economic growth and ecological preservation.